Effect of cooling water temperature on the temperature changes in pulp chamber and at handpiece head during high-speed tooth preparation - Ra'fat I. Farah (Restorative Dentistry & Endodontics)
ObjectivesIt was the aim of this study to evaluate the effect of cooling water temperature on the temperature changes in the pulp chamber and at the handpiece head during high-speed tooth preparation using an electric handpiece.Materials and MethodsTwenty-eight intact human molars received a standardized occlusal preparation for 60 seconds using a diamond bur in an electric handpiece, and one of four treatments were applied that varied in the temperature of cooling water applied (control, with no cooling water, 10°C, 23°C, and 35°C). The temperature changes in the pulp chamber and at the handpiece head were recorded using K-type thermocouples connected to a digital thermometer.ResultsThe average temperature changes within the pulp chamber and at the handpiece head during preparation increased substantially when no cooling water was applied (6.8°C and 11.0°C, respectively), but decreased significantly when cooling water was added. The most substantial drop in temperature occurred with 10°C water (−16.3°C and −10.2ºC), but reductions were also seen at 23°C (−8.6°C and −4.9°C). With 35°C cooling water, temperatures increased slightly, but still remained lower than the no cooling water group (1.6°C and 6.7ºC).ConclusionsThe temperature changes in the pulp chamber and at the handpiece head were above harmful thresholds when tooth preparation was performed without cooling water. However, cooling water of all temperatures prevented harmful critical temperature changes even though water at 35°C raised temperatures slightly above baseline.